ANALISIS EXPERIENTIAL MARKETING DAN DAMPALNYA TERHADAP KEPUASAN KONSUMEN (STUDI KASUS: KOPI IRENG DAGO BANDUNG) - Dewanta Facrureza; Nita Christina (Akademi Pariwisata Bunda Mulia, 2023)
The growth of the culinary business in the city of Bandung, which is increasingly developing, has led to business competition, especially in the type of coffee shop business category. Every business actor is required to understand what consumers need and make consumers feel satisfied. There is an experiential marketing approach to marketing that engages consumer emotions that create memorable experiences. The purpose of this study was to determine the level of customer satisfaction on the effect of experimental marketing carried out by Kopi Ireng Dago Bandung.To investigate this, the researcher used a quantitative research method with a total sample size of 100 respondents who were selected by non-probability purposive sampling technique, which were consumers who had visited Kopi Ireng Dago Bandung. The data processing analysis method used is the validity test, reliability test, classic assumption test (normality and multicollinearity), hypothesis testing (partial and simultaneous significance test) and multiple linear analysis.Based on the t table distribution of 0.025: 93, the t table value is 1.9850. The results of the partial significance test (t-test) show that 3 of the 5 hypotheses tested in this study are accepted and have a partial effect on customer satisfaction, including the Feel (X2) variable with a t-count value of 2.087> t table 1.9850, the variable Act ( X4) with t count value 2,340> t table 1.9850, and Relate (X5) with t count value 3.062> t table 1.985. The simultaneous significance test (f-test) shows that f count 17,247> f table 2.31 with a significance level of 0.000 <0.05, which means that the experiential marketing variable dimensions consisting of Sense, Feel, Think, Act, and Relate have a significant effect on customer satisfaction. The coefficient of determination test results showed that experiential marketing had a effect of 47,8% on customer satisfaction at Kopi Ireng Dago Bandung.